Avrupa Birliği sürecinde Avrupa Siyasi Partileri (European Political Parties in the Process of European Union) - Hüseyin GÜL (Dokuz Eylül Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2009)
Political parties at the European level are important as a factor of integration within the Union. They contribute to forming a European awareness and to expressing the political will of the citizens (Treaty on European Union, Article 138a). It is also problematic, as these parties do not constitute a European party system above the article. The article traces the development of transnational cooperation link among the parties of the European Parliament from 1952 to days, illustrates that, from the earliest stages of European integration, organizational structure and norms that were transnational and supranational in style and representation.